"There's no way we can teach all of this": Factors that influence secondary history teachers' content choices. (3rd April 2021) - Girard, Brian; Harris, Lauren McArthur; Mayger, Linda Kay; Kessner, Taylor M.; Reid, Stephanie
ABSTRACT: This mixed-methods study explored the factors secondary history teachers use to determine historical content for their classrooms and the degree of perceived control in decision-making. Through a survey ( N = 260) and follow-up interviews ( n = 23), we found that secondary history teachers in the United States ranked historical significance most highly in their curricular decision-making, but the extent to which teachers felt they were able to exert control over curricular decisions was influenced by required assessments and other contextual factors. Nevertheless, many teachers also prioritized student interest and relevance when choosing historical content. Interviews revealed complexity in teachers' thinking and additional context-specific (dis)incentives (e.g., fear of controversy) regarding curricular choices. Implications for teacher education and policy are emphasized.